STRATEGI PERENCANAAN EFEKTIVITAS PADA REVITALISASI PASARCIPUTAT - Nur Fauziah Latif; Salsabila Rahmadina, Muhammad Farsya Razaq, Dina Khaerunnisa, Mawar (Adisam Publisher, 2024)
This research discusses the effectiveness planning strategy in the revitalization of Ciputat Market, by the South Tangerang City government. There are several problems that need to be addressed, such as the inadequate physical condition of the market, the presence of street vendors outside the market, and illegal levies received by traders. This study aims to identify the problems faced by traditional markets that are accepted by traders and evaluate the steps that can be taken to improve the effectiveness of market revitalization. Some of the effectiveness planning strategies that can be used in market revitalization include physical improvement of the market, rearrangement of traders, and handling illegal levies. In addition, environmental and needs analysis, handling illegal levies and extortion against street vendors. The issue of illegal levies (pungli) is still a rampant problem in Ciputat market, and partnerships with the private sector and third parties are expected to support the market revitalization process. Continuous evaluation is also considered important to track the progress and effectiveness of the revitalization efforts. Thus, the conclusion is to emphasize the importance of effective planning strategies, handling illegal levies, partnerships with private and third parties, and continuous evaluation in Ciputat Market revitalization efforts.